The association between harm avoidance personality traits and self-reported concussion history in South African rugby union players. Issue 1 (January 2018) - Mc Fie, Sarah; Abrahams, Shameemah; Patricios, Jon; Suter, Jason; Posthumus, Michael; September, Alison V.
Abstract: Objectives: Personality traits have been proposed to affect the risk of sports concussion, but evidence is limited. Cloninger's Tridimensional Personality Questionnaire (TPQ) measures novelty seeking, harm avoidance (HA), and reward dependence traits. The aim of this study was to investigate the relationship between TPQ scores and concussion history in rugby union players. Design: Cross-sectional study. Methods: Rugby players from high schools, senior amateur clubs, and professional teams provided a self-reported concussion history and completed the TPQ. Participants reporting no previous concussions formed the control group, while participants reporting concussion formed the case group. A one-way analysis of covariance, with age as a covariate, was used to examine the differences in TPQ scores between groups. Results: Of the 309 participants, 54% reported a minimum of one concussion (junior: 47%; amateur: 52%; professional: 72%). HA scores were significantly higher in junior players without a history of concussion compared to cases (p = 0.006). Specifically, the junior control group had higher "anticipatory worry" (p = 0.009) and "fear of uncertainty" (p = 0.008). In contrast, the professional control group had lower HA scores than cases (p = 0.009), while the amateur cohort displayed no differences between control and case groups. Conclusions: This study identified a novel association between HA and concussion in rugby players, adding evidence to the role of personality in a multifactorial risk-model of concussion. The findings suggest that lower HA may lead to increased dangerous play in youth rugby, influencing concussion susceptibility. Contrasting associations in the professional cohort suggest further research is required to understand the role of personality in concussion.